2018
DOI: 10.1177/2329048x18798255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transcranial Direct Current Stimulation on Reading Skills of Children and Adolescents With Dyslexia

Abstract: Introduction:Rehabilitation techniques have been used to facilitate reading acquisition in dyslexia. However, many individuals continue to present academic impairment throughout life. New intervention strategies are necessary to further help this population.Objectives:Assess the impact of transcranial direct current stimulation on reading skills in children and adolescents with dyslexia.Methods:The study was conducted with one-group pretest–posttest. Participants received 2 mA transcranial direct current stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
2
28
1
4
Order By: Relevance
“…The possibility to modulate reading in individuals with and without dyslexia using transcranial electrical stimulation, such as tDCS, has been documented in the literature [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Nevertheless, the underlying neurocognitive mechanisms mediating reading changes induced by tDCS are still not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility to modulate reading in individuals with and without dyslexia using transcranial electrical stimulation, such as tDCS, has been documented in the literature [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Nevertheless, the underlying neurocognitive mechanisms mediating reading changes induced by tDCS are still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the positive effect of tDCS on reading [ 54 , 55 , 56 ] and, particularly, in dyslexia [ 57 , 58 , 59 , 60 , 61 , 62 ]. In typically reading adults, an overall improvement in word reading efficiency has been observed after the application of left anodal/right cathodal tDCS over the temporo-parietal areas [ 54 ] as well as following left anodal stimulation over the inferior parietal lobule [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] The anodic tDCS is based on an electric current from a generator that aims to stimulate certain cortical areas, causing an increase in local cerebral blood flow. [ 25 ] This tool has been currently used in the treatment of various psychiatric and neurological disorders such as schizophrenia, [ 26 ] dyslexia, [ 27 ] autism, [ 28 ] cerebellar ataxia, [ 29 ] epilepsy, [ 30 ] unipolar and bipolar depression, [ 31 ] since it is considered safe and relatively less expensive than other noninvasive brain stimulation approaches. [ 32 , 33 ] Advantages of the cost-effectiveness of tDCS could be even more important considering low-middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Cancer and Antonietti (2018) published a review of studies that examined the effect of tDCS on reading or spelling outcomes (see Appendix A for a summary of relevant studies). These studies can be categorised according to whether they administered (1) single tDCS stimulation before or during a reading or spelling assessment (Before: Boehringer, Macher, Dukart, Villringer, & Pleger, 2013;Costanzo, Varuzza, Rossi, Sdoia, Varvara, Oliveri, Koch, et al, 2016a;Cummine et al, 2019;Heth & Lavidor, 2015;Rios et al, 2018;Turkeltaub et al, 2012;Younger, Randazzo Wagner, & Booth, 2016;During: Thomson et al, 2015;Westwood et al, 2017); or (2) repeated stimulation during reading or spelling training (Costanzo et al, 2016b(Costanzo et al, , 2018. Most of these studies administered anodal stimulation over left-hemisphere regions which are thought to be associated with reading ability (e.g., temporo-parietal cortex, posterior temporal lobe, inferior frontal gyrus, occipital visual cortex), with cathodal or reference electrodes position over the right hemisphere (i.e., temporo-parietal cortex, orbitofrontal cortex) or on the right cheek.…”
mentioning
confidence: 99%